Pemanfaatan Restful Api Pada Mobile based test Untuk Sertifikasi Karyawan - Anggraini Kusumaningrum; Asih Pujiastuti; Satya Wira Wicaksana; Yuliani Indrianingsih; Mardiana Irawaty (Jurnal Teknologi Informasi dan Terapan, 2022)
A test is something that is used to test the quality of intelligence, ability, learning outcomes and so on. The test is always associated with an assessment or evaluation of a person to determine the person's mastery of the material. The rapid development of the digital world makes it easier for people to complete their work, the use of mobile tests is one of the technologies used by using the Application Programming Interface (API). Restful API is one of the architectures in the API which has 4 important components, namely URL Design, HTTP Verbs, HTTP Response Code, and Response Format. Rest client will access data to the Rest server, each data is distinguished based on Global ID or Universal Resource Identifier (URI) in the form of formal text XML or JSON. From the test results using WhiteBox on the admin side, there are 4 paths for 3 days with 100% success. While on the client side there are 8 paths for 3 days with 100% success.